The Analgesic Effects of Static Magnetic Fields. Issue 2 (28th January 2021) - Fan, Yixiang; Ji, Xinmiao; Zhang, Lei; Zhang, Xin
Abstract : Pain is one of the most common reasons why people seek medical care, which is related to most disease states. Magnetic fields (MFs) can be applied locally to specific parts of human bodies with high penetration and temporal control, which have a long‐debated history in folk therapy. The purpose of this review is to collect and analyze experimental data about the analgesic effects of static magnetic fields (SMFs) so that we can have a scientific understanding regarding this topic. We collected 28 studies (25 English and 3 Chinese papers) with proper sham controls that investigated the effects of SMFs on pain relief in humans or mice. We found that 64% of the human studies and all mice studies in the literature showed positive analgesic effects of SMFs, which are related to factors including SMF intensity, treatment time, and pain types. Higher intensity and/or longer treatment time, as well as some specific pain types, may have better pain relief effects. Initial mechanistic studies indicated that membrane receptors, such as capsaicin receptor VR1/TRPV1, opioid receptors, and P2X3 receptors, might be involved. By describing experimental evidence and analysis, we found that SMFs actually hold considerable promise for managing some specific types of pain if proper SMF parameters are used. More studies comprehensively evaluating the parameters of SMF and its corresponding analgesic effects on different pain types, as well as the underlying molecular mechanisms, will be necessary to further validate its therapeutic potential in pain management in the future. Bioelectromagnetics. 00:00–00, 2021. © 2021 Bioelectromagnetics Society